The Functioning and Use of Large Language Models and Related Copyright Issues: the Case of the ChatGPT Tool - Ovčak Kos, Maja; Grošelj, Darja (Digital Platforms: Legal And Economic Challenges, 2024)
We examine the functioning and use of large language models and related copyright issues, focusing on ChatGPT. ChatGPT is a generative general artificial intelligence system. The model is trained on large amounts of data whose origin and use are not well defined, and the final product is tailored to the context that the model inferred from the conversation. From a copyright perspective, we focus on the questions of whether a product created using ChatGPT is a work of authorship, and if so, who is the author, and whether the use of a ChatGPT-created product may infringe copyright in existing works of authorship. If users freely and creatively choose when using the ChatGPT tools meets the standard of individuality, the product may be a work of authorship. When assessing the infringement of copyright on existing works, it is essential to distinguish between imitation of style and reproduction.